Efficacy of manual articular vertebral therapy in patients with migraine (European Journal of Health Research, 2019)
Migraine is one of the most common nervous system disorders and it is the third cause of disability in under 50s. Migraine treatment using manual vertebral articulatory therapy (MVAT) may be effective, however, there ir more controversy than in other types of headaches. The objective of this study is to assess the changes produced after the application of MVAT in patients with migraine in terms of pain intensity and its impact. 44 participants with a mean age of 39 years (standard deviation= 9.47) with migraine, were divided into two groups randomly: 1) MVAT group (n= 22), 2) control group (n= 22). Two evaluations were carried out, pretreatment and post-treatment, and the Visual Analog Scale (VAS) and the Headache Impact Questionnaire (HIT-6) were used. There were no significant differences between the two factors (i.e. time and group measures) in either VAS or HIT6 (p> 0.05), however, there were significant differences in the MVAT group between pretreatment and post-treatment. post-treatment in VAS (p= 0.004) and in HIT-6 (p= 0.014). MVAT in patients with migraine, decreases the intensity of pain and the impact associated with migraine, and could be an appropriate treatment in combination with medication.